First MEPS/HPLC assay for the simultaneous determination of venlafaxine and O-desmethylvenlafaxine in human plasma. (November 2014) - Magalhães, Paulo; Alves, Gilberto; Rodrigues, Márcio; LLerena, Adrián; Falcão, Amílcar
Background: A new high-performance liquid chromatography–fluorescence detection assay based on microextraction by packed sorbent as sample preparation approach is described to quantify venlafaxine (VEN) and its main metabolite [ O -desmethylvenlafaxine (ODV)]in human plasma.Methods & results: Chromatographic separation of the target analytes (VEN and ODV) and internal standard (licarbazepine) was achieved in less than 6 min on a reverse-phase C18 column using isocratic elution. Calibration curves were linear in the ranges of 10–1000 ng ml -1 for VEN and 20–1000 ng ml -1 for ODV. The method was successfully applied to real plasma samples.Conclusion: This microextraction by packed sorbent/high-performance liquid chromatography–fluorescence detection assay offers a cost-effective tool that can be applied for therapeutic drug monitoring and also support other pharmacokinetic-based studies in humans.